Identification and characterization of circRNAs related to meat quality during embryonic development of the longissimus dorsi muscle in two pig breeds - Wang, Jing; Chen, Jun-Feng; Ma, Qiang; Mo, De-Lin; Sun, Jia-Jie; Ren, Qiao-Ling; Zhang, Jia-Qing; Lu, Qing-Xia; Xing, Bao-Song (Frontiers in Genetics, 2022)
Meat quality, an important economic trait, is regulated by many factors, especially by genetic factors, including coding genes, miRNAs, and lncRNAs. Recent studies have elucidated that circRNAs also play a key role in muscle development and lipid deposition. However, the functions and regulatory mechanisms of circRNAs in meat quality remain mostly unknown. The circRNA expression profiles between Huainan pigs (Chinese indigenous pigs, fat-type, HN) and Large White pigs (Western commercial pigs, lean-type, LW) in the longissimus dorsi (LD) muscle at 38, 58, and 78 days post conception (dpc) were compared by sequencing. In total, 39,887 circRNAs were identified in 18 samples, and 60, 78, and 86 differentially expressed circRNAs (DECs) were found at the three stages mentioned above between these two breeds. The parent genes of DECs were enriched in myogenesis, proliferation, adipogenesis and muscle fiber-type transition. The circRNA-miRNA interaction networks included 38 DECs and 47 miRNAs, and these miRNAs were involved in muscle development and lipid metabolism. Two shared DECs (circ_0030593 and circ_0032760) of these three stages were selected, their head-to-tail junction sites were validated by Sanger sequencing, and RT‒qPCR results suggested that these two DECs might be involved in intramuscular fat deposition. These findings provide a basis for understanding the role of circRNAs in meat quality.